Factors Influencing Environmental Disclosure with Integrated Corporate Governance as a Moderating Variable - Yuha Nadhirah Qintharah; Yvonne Augustine (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to identify the factors influencing environmental disclosure, with integrated corporate governance serving as a moderating variable. A quantitative approach is used, employing statistical software for data analysis. The study examines companies listed on the Indonesia Stock Exchange across various sectors—including mining, basic and chemical industries, consumer goods, and others—covering the period from 2018 to 2022. The sample includes 482 companies. The findings reveal that environmental costs positively impact environmental disclosure, while carbon emission disclosure does not affect it. Furthermore, governance strengthens the link between environmental costs and environmental disclosure but does not influence the relationship between carbon emission disclosure and environmental disclosure. These results provide valuable insights for the government to enhance both the quantity and quality of environmental disclosures among Indonesian companies. Keywords: Environmental Disclosure, Intergrated Corporate Governance, Environmental Cost, Corporate Carbon Disclosure,